2006
DOI: 10.1352/0895-8017(2006)111[417:bcaocw]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Broad Cognitive Abilities of Children With Mental Retardation: An Analysis of Group and Individual Profiles

Abstract: Group and individual broad ability profiles of children with mental retardation and a matched sample of children with average achievement was investigated through use of the 7 Cattell-Horn-Carroll (CHC) factor clusters from the Woodcock-Johnson III Tests of Cognitive Abilities. Results indicate that, as a group, the ranked performance of the children with mental retardation on the CHC factor clusters was largely consistent with the clusters' g loadings. When compared to average-achieving matches, the children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…What is known is that students with ID comprise a very diverse group and each student has specific educational needs (Rhodes et al, 2015). Their cognitive and adaptive limitations vary from person to person and as a population, they are characterised by a variety of strengths and weaknesses in broad abilities (Bergeron & Floyd, 2006). For this reason, it is not possible to either draw a typical profile of people with ID or specify standard features of their personality or behaviour (Westwood, 2011).…”
Section: Mathematics Curricula Development For Students With Idmentioning
confidence: 99%
“…What is known is that students with ID comprise a very diverse group and each student has specific educational needs (Rhodes et al, 2015). Their cognitive and adaptive limitations vary from person to person and as a population, they are characterised by a variety of strengths and weaknesses in broad abilities (Bergeron & Floyd, 2006). For this reason, it is not possible to either draw a typical profile of people with ID or specify standard features of their personality or behaviour (Westwood, 2011).…”
Section: Mathematics Curricula Development For Students With Idmentioning
confidence: 99%
“…Measuring cognitive functioning based on performance on tasks that assess specific abilities has proven more meaningful than determining Intelligence Quotient (IQ) alone, which reflects total score on the intelligence test. This can be partially explained by the development and revision of theories and models underlying the construction of intelligence tests (Bergeron et al, 2006;Schneider & McGrew, 2012). The Cattell-Horn-Carroll (CHC) psychometric model of cognitive abilities is based on 16 major domains, including fluid intelligence (Gf), comprehension/knowledge (Gc), visual processing (Gv), auditory processing (Ga), processing speed (Gps), shortterm memory (Gsm) and long-term storage and retrieval (Glr).…”
mentioning
confidence: 99%
“…These broad domains are underpinned by 70 specific factors, assessed by the items of the tests (Schneider & McGrew, 2012). Bergeron et al (2006) highlight that the different cognitive abilities have distinct degrees of importance for overall intellectual functioning. This depends on how much a given specific ability explains (correlates with) general intelligence.…”
mentioning
confidence: 99%
“…Previous studies testing cognitive abilities in AB and II-children also found a large variety of performance patterns in the population with II (Bergeron & Floyd, 2006). Also, far from testing conditions, II-basketball players presented a higher variability in game-related statistics than AB-players during competition .…”
Section: Time (S)mentioning
confidence: 83%
“…Parts in this system are interrelated and a deficit in any part will likely affect the functioning of the entire system. However, the degree to which an impaired cognitive ability lowers the functioning of the whole system is not similar for all cognitive abilities and it depends on the affected ability´s centrality on G-factor (Bergeron & Floyd, 2006). According to this, an athlete with impairment in cognitive abilities relevant in sport performance but with low centrality (low implication on G-factor) could have more limitations to perform a sport than an athlete whit more impaired G-factor but not these cognitive abilities.…”
mentioning
confidence: 99%